miR-543 promotes colorectal cancer proliferation and metastasis by targeting KLF4 - Zhai, Fangbing (Oncotarget, 2017)
Till now, miR-543 expression has been demonstrated to be involved in the development of some cancers. However, reports about its expression and mechanism in colorectal cancer (CRC) were conflicting [1, 2]. Here, we investigated clinical implications of miR-543 and mechanisms underlying miR-543-mediated CRC development. In this study, real-time quantitative PCR (qRT-PCR) validated miR-543 was highly expressed in CRC samples and cell lines. MiR-543 was closely associated with tumor size, TNM stage and metastasis. In addition, survival analysis showed that high miR-543 expression was obviously correlated with poor overall survival and disease-free survival. Mechanically, downregulation of miR-543 by miR-543 inhibitor obviously repressed cell proliferation, promoted apoptosis, affected migration and invasion. Moreover, luciferase reporter analysis identified that Krüppel-like Factor-4 (KLF4) was a direct target of miR-543, and there was an obvious inverse correlation between miR-543 and KLF4 expression in CRC tissues. Furthermore, KLF4 down-regulation favors miR-543-induced oncogenic effect on cell proliferation, apoptosis, migration, and invasion. In conclusion, this study indicated that miR-543 facilitates colorectal cancer proliferation and metastasis by targeting KLF4, and miR-543 may serve as a promising target for the treatment of CRC patients.